Spatial and temporal patterns of cholera outbreaks in Sri Lanka - Ratnayake, R.M.K. (ResearchGate, 2017)
Attached

Among the medical health problems faced by Sri Lanka, the prevalence of cholera is in many parts of the island. Although in the recent past cholera was not considered a dreaded disease, the country had experienced a recorded history of cholera back from 1841. From time to time cholera reached epidemic proportions. Regional variations can also be observed in the distribution of the disease during those periods. The objective of this study is to analyse the spatial and temporal pattern of the cholera outbreak in Sri Lanka. Data for the study was obtained from numerous secondary sources, unpublished theses and from filed work conducted in North Colombo and the Kurunegala District. Two major high risk areas were identified viz; the underserved areas in the Colombo and suburban area and the Dry Zone district. In urban areas, there are lack of sanitation facilities and in Dry Zone the floods and drought is the main courses for the cholera epidemic.
Keywords: cholera, epidemic, disease, sanitation, medical geography